Ampeliscid crustaceans (Amphipoda: Gammaridea: Ampeliscidae) from the Vietnam sea - Thanh, Dang Ngoc; Anh, Le Hung (Academia Journal of Biology, 2013)
Thirty-five species of the family Ampeliscidae, including 22 species of Ampelisca and 13 species of Byblis are listed for the near-shore waters of Vietnam. In the world, Ampelisca compreses more than 210 species and 83 species of Byblis. Ten species are newly recorded for the benthic Ampeliscidae fauna of the Vietnam sea, of which six new species are described, viz. Ampelisca dongnamensis; Ampelisca submisakiensis; Ampelisca talus; Ampelisca taynamensis; Ampelisca thaoae and Byblis caecus. Some remarks on their geographical distributions are presented in the paper. <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: SimSun; mso-ansi-language: EN-AU; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-AU">Thirty-five species of the family Ampeliscidae, including 22 species of Ampelisca and 13 species of Byblis are listed for the near-shore waters of Vietnam. In the world, Ampelisca compreses more than 210 species and 83 species of Byblis. Ten species are newly recorded for the benthic Ampeliscidae fauna of the Vietnam sea, of which six new species are described, viz. <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Ampelisca dongnamensis<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: SimSun; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">; Ampelisca submisakiensis; Ampelisca talus; Ampelisca taynamensis; Ampelisca thaoae and Byblis caecus<span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: SimSun; mso-ansi-language: EN-AU; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;" lang="EN-AU">. Some remarks on their geographical distributions are presented in the paper.